Serumal and Salivary 25(OH)D and 1,25(OH)D Levels of Head and Neck Cancer Patients - Dina Keumala Sari; Liza Meutia Sari; Lidya Imelda Laksmi; Farhat Farhat; Elvita Rahmi Daulay; Ferry Sandra; Zulfikar Lubis; Ratna Akbari Ganie (The Indonesian Biomedical Journal, 2021)
BACKGROUND: Saliva has been suggested as a substitute of serum for the detection of 25 Dihydroxyvitamin D (25(OH)D) in healthy people. However, investigation of salivary 1,25(OH)D has not been clearly reported. Vitamin plays important roles in inhibiting cancer progression. Current study was conducted to investigate serumal and salivary 25(OH)D) and 1,25(OH)D levels of healthy and head and neck cancer (HNC) subjects.METHODS: Research were conducted at Haji Adam Malik Hospital, Medan, Indonesia. Forty HNC and 40 healthy subjects were recruited and selected based on inclusion and exclusion criteria. Medical records were documented, followed by anthropometric evaluation and serum and saliva collection. Laboratory investigation for 25(OH)D and 1,25(OH) was performed using Enzyme-linked immunosorbent assay (ELISA) methods.RESULTS: Significant serumal (p=0.002) and salivary (p=0.016) 25(OH)D mean level differences of HNC and normal groups were obtained. More serumal or salivary 25(OH)D deficient subjects were found in control group than those in HNC group. Meanwhile, serumal and salivary 1,25(OH)D mean levels of HNC group were not significantly different with the ones of control group. There were significant correlations of serumal-salivary 25(OH)D as well as serumal-salivary 1,25(OH)D levels in normal group.CONCLUSION: Serumal and salivary 25(OH)D and 1,25(OH)D levels of HNC group were relatively normal. Salivary 25(OH)D and 1,25(OH)D could be suggested as substitutes for serumal ones.KEYWORDS: vitamin D, 25(OH)D, 1,25(OH)D, head and neck cancer